2023
DOI: 10.1093/ve/vead014
|View full text |Cite
|
Sign up to set email alerts
|

H9N2 avian influenza virus dispersal along Bangladeshi poultry trading networks

Abstract: Avian influenza virus subtype H9N2 is endemic in Bangladesh’s poultry population. The subtype affects poultry production and poses a potential zoonotic risk. Insufficient understanding of how the poultry trading network shapes the dissemination of avian influenza viruses has hindered the design of targeted interventions to reduce their spread. Here, we use phylodynamic analyses of haemagglutinin (HA) sequences to investigate the spatial spread and dispersal patterns of H9N2 viruses in Bangladesh’s poultry popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…The inter-mingling of different types of birds from potentially distant locations is concerning when associated to co-circulation of genetically distinct viruses. A recent phylodynamics study found substantial genetic structuring of H9N2 AIV by city in Bangladesh [55], compatibly with low overlap between the corresponding supplying production PLOS COMPUTATIONAL BIOLOGY areas [18]. In contrast, viral lineages appeared to be highly mixed across LBMs within the same city, possibly indicating frequent connections between these markets.…”
Section: Discussionmentioning
confidence: 94%
“…The inter-mingling of different types of birds from potentially distant locations is concerning when associated to co-circulation of genetically distinct viruses. A recent phylodynamics study found substantial genetic structuring of H9N2 AIV by city in Bangladesh [55], compatibly with low overlap between the corresponding supplying production PLOS COMPUTATIONAL BIOLOGY areas [18]. In contrast, viral lineages appeared to be highly mixed across LBMs within the same city, possibly indicating frequent connections between these markets.…”
Section: Discussionmentioning
confidence: 94%
“…The inter-mingling of different types of birds from potentially distant locations is concerning when associated to co-circulation of genetically distinct viruses. A recent phylodynamics study found substantial genetic structuring of H9N2 AIV by city in Bangladesh [ 55 ], compatibly with low overlap between the corresponding supplying production areas [ 18 ]. In contrast, viral lineages appeared to be highly mixed across LBMs within the same city, possibly indicating frequent connections between these markets.…”
Section: Discussionmentioning
confidence: 99%
“…Sonali [crossbred of Fayoumi female and RIR (Rhode Island Red) male], Deshi (the breeds of chickens native to Bangladesh) ( 57 ). On the other hand, domestic ducks were mainly acquired from other LBMs and purchased from a greater distance ( 58 ). Consequently, understanding the trading pattern of turkey is critical.…”
Section: Discussionmentioning
confidence: 99%